2004
DOI: 10.1557/proc-852-oo3.1
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Mechanical Properties of Aging Oil Paints

Abstract: The stiffening and embrittlement of oil paints over time has been a real concern for those responsible for the long term care and preservation of paintings. This paper examines the effects of time, pigments, relative humidity (RH), temperature and solvents on the mechanical properties of traditional oil paints. In this way it is possible to determine the role of each factor in causing the paints to become brittle. Even after 14 years the oil paints show little evidence that the long term "maturing" processes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 8 publications
3
49
0
Order By: Relevance
“…Zinc white paint is usually described as a very brittle paint compared to paints based on other pigments. Indeed, previously reported that zinc white oil paint is a stiff and brittle paint, with a very high Young modulus (1.7 GPa), significantly higher than lead white paint (Young modulus of 0.3 GPa) [5]. Our nanoindentation results are therefore fully consistent with the tensile test results.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Zinc white paint is usually described as a very brittle paint compared to paints based on other pigments. Indeed, previously reported that zinc white oil paint is a stiff and brittle paint, with a very high Young modulus (1.7 GPa), significantly higher than lead white paint (Young modulus of 0.3 GPa) [5]. Our nanoindentation results are therefore fully consistent with the tensile test results.…”
Section: Discussionsupporting
confidence: 91%
“…Our nanoindentation results are therefore fully consistent with the tensile test results. Fuesers and Zumb眉hl (2008) studied the impact of up to 14 year aging on the mechanical properties of free paint films [5,11]. No saturation of the mechanical response is observed over this long aging time so that extrapolation to centuries is difficult.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations